David Lynch - Nieland, Justus (Contemporary film directors., 2012)
Discussing the major films of this iconic director, Justus Nieland explores the range of modern design idioms that inform David Lynch's famously cinematic interiors, his work's acute attention to the shaping of affect in particular media environments, and its insistence on the strangeness of biology lived through media. Nieland resituates Lynch's experimentalism in three ways: first, by taking seriously Lynch's status as a surrealist, and by extension, exploring the status of surrealism in contemporary media culture; second, by placing Lynch's cultural production in a broader tradition of modern Romanticism; and third, by offering a sustained treatment of Lynch's aesthetics in the context of a specifically modernist and avant-garde tradition. By examining such major works as Eraserhead, Blue Velvet, Twin Peaks, Mulholland Drive, and Inland Empire, Nieland provocatively argues that the romantic transcendental impulse in Lynch is an historical function of modernity, which, in its efforts to erect a divide between nature and culture, produces a longing for a host of transcendental "outsides" and yields all the monstrous hybrids of nature and culture that populate the Lynchian universe